2019
DOI: 10.3390/agronomy9120849
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autumn Foliar Fertilization on the Yield and Quality of Winter Oilseed Rape Seeds

Abstract: This paper presents the results of a 3-year field experiment conducted in north-eastern (NE) Poland to determine the influence of the autumn application of foliar macronutrient and micronutrient fertilizers (control, one application in BBCH (Biologische Bundesanstalt, Bundessortenamt and Chemische Industrie) stage 16 (six leaves unfolded)), two applications in BBCH stages 14 (four leaves unfolded), and 16 (six leaves unfolded) on the growth and development of winter oilseed rape plants, nutrient accumulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…The authors showed that on a treatment without biostimulants, the concentration of harmful compounds was the highest and averaged to 10.15 µM·g −1 . In other studies by Jankowski et al [18], intensified foliar fertilization significantly reduced progoitrin levels by 41% on average and gluconapin by 46% on average, while in subsequent studies [19], the foliar fertilizers used increased the content of alkene and indole glucosinolates in the dry matter of seeds. Similarly, Filipek-Mazur et al [21], after applying fertilizers containing sulphur, while Davoudi et al, [23] after applying selenium, showed an increase in glucosinolate content in rapeseed.…”
Section: The Content Of Glucosinolates Depending On the Type Of Foliamentioning
confidence: 84%
See 3 more Smart Citations
“…The authors showed that on a treatment without biostimulants, the concentration of harmful compounds was the highest and averaged to 10.15 µM·g −1 . In other studies by Jankowski et al [18], intensified foliar fertilization significantly reduced progoitrin levels by 41% on average and gluconapin by 46% on average, while in subsequent studies [19], the foliar fertilizers used increased the content of alkene and indole glucosinolates in the dry matter of seeds. Similarly, Filipek-Mazur et al [21], after applying fertilizers containing sulphur, while Davoudi et al, [23] after applying selenium, showed an increase in glucosinolate content in rapeseed.…”
Section: The Content Of Glucosinolates Depending On the Type Of Foliamentioning
confidence: 84%
“…After applying foliar fertilization with sulphur and boron in combination with amino acids (4), the value of this feature increased by an average of 1.25 µM/g, while the smallest (average of 1.00 µM·g −1 ) increase in the GLS concentration was recorded in treatment 3, where sulphur and boron were used. Jankowski et al [17], thanks to the effect of foliar feeding with boron, observed a significant increase in the content of alkene glucosinolates (progoitrin) and a decrease in indole GLS (4-OH-glucobrassicin), and in later studies of the authors [19], under the influence of autumn macro and micronutrient feeding, an increase in the content of alkenyl and indole glucosinolates in rapeseed seeds was observed.…”
Section: The Content Of Glucosinolates Depending On the Type Of Foliamentioning
confidence: 87%
See 2 more Smart Citations
“…; Sokólski, M.; Szatkowski, A. [2], were conducted a 3-year field experiment in north-eastern (NE) Poland to determine the influence of the autumn application of foliar macronutrient and micronutrient fertilizers on the growth and development of winter oilseed rape plants, nutrient accumulation, overwintering success, yield components, yield, nutritional value, and feed value of seeds confirmed that the application of foliar macronutrient and micronutrient fertilizers in autumn increased seed yield (by 0.25 Mg ha−1), contributed to a significant increase in the crude fat content of seeds (by 1.3-7.4 g kg−1 dry matter (DM), increased the content of oleic acid, decreased the concentration of linoleic acid, and increased the content of glucosinolates.…”
mentioning
confidence: 99%